EFEKTIVITAS EKSTRAK DAGING BUAH NANAS (ANANAS COMOSUS L.) DALAM PENURUNAN INDEKS BROWNING DARI UMBI KENTANG (SOLANUM TUBEROSUM L.) - Wardanis, Putri; Zulkifli, Zulkifli; Lande, Martha L.; Nurcahyani, Endang (Politeknik Negeri Lampung., 2019)
The purpose of this study was to determine whether the pineapple fruit extract can inhibit theprocess of browning on the potato tubers. This study used Completely Randomized Design(RAL) with 5 levels of pineapple fruit concentration of 0% v/v, 25% v/v. 50% v/v, 75% v/v,and 100% v/v and consist of 5 replications. Qualitative Parameters in this study was the colosurface of potato tubers while quantitative parameters were browning index, total soluble carbohydrate content, and dehydrogenase enzyme activity homogeneity of variance, analysisof variance, and Tukey test were conducted at 5% significant level. Correlations betweendependent and independent variables were determined by linear regression. The resultshowed that the color surface of potato tuber treated with the concentration of pineappleextract 100% v/v was less brown than control and other concentrations. Index browning ofpotato tuber treated with concentration 75% v/v and 100% v/v was significantly decreased. Concentration of pineapple extract was negative linearly correlated to browning index ofpotato tubers. The concentration of pineapple extract 100% v/v increased significantly totalsoluble carbohydrate of potato tubers. The concentration of pineapple extract was positivelinearly correlated to total soluble carbohydrate. The activity of dehydrogenase enzyme ofpotato tuber treated with concentration 100% v/v was significantly increased. Theconcentration of pineapple extract was quadratic correlated to the activity of dehydrogenaseenzyme.